2016
DOI: 10.1016/j.jagp.2015.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Neuropsychiatric Symptoms in Mild Cognitive Impairment and Risk of Dementia

Abstract: Objectives To identify clusters of patients with incident mild cognitive impairment based on their neuropsychiatric symptoms (NPS) and to examine the risk of progression to dementia, based on these clusters. Design Cohort study with 2 years median length follow-up. Setting: Alzheimer’s disease Centers from the National Alzheimer’s Coordinating Center (NACC). Participants Patients with MCI who were at least 60 years old with complete data and follow-up (n = 540). Measurements Latent class analysis was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
63
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 42 publications
5
63
1
1
Order By: Relevance
“…This relationship was not apparent for MCI or CN-AR. The results are consistent with previous reports that dementia diagnosis is associated with a greater number of NPS [4,8,19]. Studies of longitudinal trajectories of NPS from MCI to dementia [24,38] report that although most of those with MCI (90%) demonstrate a low NPS burden that is stable over time [38], those who demonstrate increasing NPS burden (7%) or a high NPS burden at baseline have a 1.74 [38] to 2.55 [24] fold increase in risk of progression to dementia at follow-up.…”
Section: Symptom Burdensupporting
confidence: 93%
See 4 more Smart Citations
“…This relationship was not apparent for MCI or CN-AR. The results are consistent with previous reports that dementia diagnosis is associated with a greater number of NPS [4,8,19]. Studies of longitudinal trajectories of NPS from MCI to dementia [24,38] report that although most of those with MCI (90%) demonstrate a low NPS burden that is stable over time [38], those who demonstrate increasing NPS burden (7%) or a high NPS burden at baseline have a 1.74 [38] to 2.55 [24] fold increase in risk of progression to dementia at follow-up.…”
Section: Symptom Burdensupporting
confidence: 93%
“…This NPS-class is similar to the symptom pattern commonly reported in studies of MCI samples [5,8,19,24,39,40], and also the 'affective' cluster reported in studies of dementia samples [18]. In our study, 28% of all those with dementia (n = 11) and 19% of those with MCI (n = 25) were classified as having an affective/low comorbidity NPS pattern.…”
Section: Clusters Of Neuropsychiatric Symptomssupporting
confidence: 88%
See 3 more Smart Citations